DEVELOPMENT OF INDEPENDENT STUDENTS AND THEIR EFFECTS IN BUILDING ISLAMIC CHARACTER - Lilis Kholisoh Nuryani (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aimed to determine the development of independent santri and its influence in building the character of Islamic students. The research method used is descriptive quantitative, which is carried out at the Arrisalah Ciamis Islamic Boarding School, with the research population being 40th-grade students. The results showed that the development of independent santri has a strong and positive influence on the development of the Islamic character of the santri. All aspects of the values contained in independent santri can be built through continuous coaching, thus helping in the development of Islamic character that reflects the nature of the Prophet Muhammad, namely Sidiq, Amanah, Tabligh, Fatonah (SATF). The conclusion is that the applicable values taught by Rasulullah SAW, namely the SATF, can be found by anyone who pursues Islamic teachings or moral education taught in Islam if the students are genuinely committed to following every pesantren fostered.